2018
DOI: 10.1093/eurheartj/ehy234
|View full text |Cite
|
Sign up to set email alerts
|

Circulating non-coding RNAs in biomarker-guided cardiovascular therapy: a novel tool for personalized medicine?

Abstract: Current clinical guidelines emphasize the unmet need for technological innovations to guide physician decision-making and to transit from conventional care to personalized cardiovascular medicine. Biomarker-guided cardiovascular therapy represents an interesting approach to inform tailored treatment selection and monitor ongoing efficacy. However, results from previous publications cast some doubts about the clinical applicability of biomarkers to direct individualized treatment. In recent years, the non-codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 82 publications
(92 reference statements)
0
51
0
Order By: Relevance
“…Apart from their use as disease biomarkers, miRNAs have also proven to be useful in evaluating patient response to the available therapies during the course of treatments and also to understand whether a patient will be responsive to a given treatment. 116 117 Also, miRNAs are being tested as drugs for cardiovascular diseases in multiple preclinical studies and have proven to be efficacious. However, considering that miRNAs and circRNAs have multiple cellular targets and may show their effects in organs not directly involved in the disease pathogenesis, attempts are being made to improve the in vivo specificity of miRNA mimics.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their use as disease biomarkers, miRNAs have also proven to be useful in evaluating patient response to the available therapies during the course of treatments and also to understand whether a patient will be responsive to a given treatment. 116 117 Also, miRNAs are being tested as drugs for cardiovascular diseases in multiple preclinical studies and have proven to be efficacious. However, considering that miRNAs and circRNAs have multiple cellular targets and may show their effects in organs not directly involved in the disease pathogenesis, attempts are being made to improve the in vivo specificity of miRNA mimics.…”
Section: Discussionmentioning
confidence: 99%
“…6 In this context, the noncoding transcriptome represents a novel and poorly explored source of diagnostic and prognostic tools for the management of cardiovascular disease (CVD). 7 In particular, circular RNAs (circRNAs), a subclass of the noncoding RNA (ncRNA) superfamily, have recently gained great interest in biomarker development. 8,9 Due to their covalently closed loop structure, circRNAs are protected from exonuclease-mediated degradation and have a longer half-life than linear RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies showed that α-synuclein levels in blood or CSF lack discrimination power and specificity ( Malek et al, 2014 ; Goldman et al, 2018 ). Next to proteins and metabolites, circulating microRNAs (miRNAs) were previously shown to be useful biomarkers in other pathologies, e.g., cancer ( Jamali et al, 2018 ) or cardiovascular disease ( de Gonzalo-Calvo et al, 2018 ). miRNAs are small non-coding RNAs involved in the regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%